Levels of Physical Activity in Nursing Students - Lázaro Dionisio Rojas Matsuda; Isaac Rodríguez Palacio; Katia Rodríguez Palacio; Ivis Espinoza Requesén; Ismaray Sacerio González; Carmen María Angulo Álvarez (Revista Finlay)
Background: the benefits of physical exercise are well known and include a lower risk of cardiovascular diseases, obesity, insulin resistance and certain types of cancer such as colon and breast cancer. Physical activity reduces the risk of obesity and is associated with mental health, emotional well-being, and increased longevity. Objective: to determine the level of physical activity developed by nursing students from the Cienfuegos University of Medical Sciences. Methods: a descriptive, cross-sectional quantitative research was carried out. The instrument used to determine physical activity was the International Physical Activity Questionnaire the long version, this instrument measures the level of physical activity in low level, moderate level and vigorous level. Results: regarding the level of physical activity, it was found that the 22.38 % of the nursing students presented a moderate level, the 8.95 % vigorous level physical activity and the 68.65 % low-level physical activity, but males are more active than females. Conclusions: an evaluation of the level of physical activity established by the international questionnaire was determined for the first time, these results being negative since the students lead a sedentary life which is detrimental to health and may affect the appearance of non-communicable diseases such as diabetes and arterial hypertension